Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.4244/eij-d-17-00359
|View full text |Cite
|
Sign up to set email alerts
|

3D printing for sizing left atrial appendage closure device: head-to-head comparison with computed tomography and transoesophageal echocardiography

Abstract: Patient-specific CT-based 3D printing models may assist device selection and prediction of device compression in the context of interventional LAA closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 22 publications
0
40
0
1
Order By: Relevance
“…Several other groups, 16,17 including ours, 11 extended the concept to more complex procedures. Wang et al 18 and Hell et al 19 demonstrated high accuracy (z100%) of printed models in predicting correct device size in two prospective cohorts (n = 75 in total). Our study confirms these findings in a larger cohort and, importantly, provides outcome analysis for recommending updates in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Several other groups, 16,17 including ours, 11 extended the concept to more complex procedures. Wang et al 18 and Hell et al 19 demonstrated high accuracy (z100%) of printed models in predicting correct device size in two prospective cohorts (n = 75 in total). Our study confirms these findings in a larger cohort and, importantly, provides outcome analysis for recommending updates in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other small reports suggest that CT may provide a more accurate measurement of the LAA and that LAA size is frequently underestimated when assessed by TOE. [26][27][28]…”
Section: Preprocedural Laa Imagingmentioning
confidence: 99%
“…Therefore, the three methods (TEE, cardiac CTA, and LAA angiography) commonly used for the clinical evaluation of the morphology and size of the LAA have their respective advantages and disadvantages. 25 Before LAA occlusion, TEE can clearly judge whether there is thrombus in the LAA and measure the basal orifice size and depth of the LAA, thereby providing the basis for the operator to select the occluder model. Cardiac CTA can achieve more objective and accurate measurement of the morphology and lobulation of the LAA and the parameters of the LAA orifice providing more sufficient basis for judging whether LAA occlusion is feasible.…”
Section: Discussionmentioning
confidence: 99%